2008
DOI: 10.1291/hypres.31.1533
|View full text |Cite
|
Sign up to set email alerts
|

A Haplotype-Based Case-Control Study Examining Human Extracellular Superoxide Dismutase Gene and Essential Hypertension

Abstract: It has been reported that oxidative stress is involved in the pathophysiology of essential hypertension (EH),which is a multifactorial disorder. Extracellular superoxide dismutase (EC-SOD) protects the human body from oxidative stress by converting the toxic superoxide anion (O2 -) into less toxic hydrogen peroxide (H2O2). In EC-SOD knockout mice, blood pressure was reported to be significantly higher than that seen in wild-type mice. The aim of this study was thus to investigate the relationship between EH an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…In the present study, the trend observed in the general population became more evident when only hypertensive patients were considered and the large differences in BP observed were replicated in the other population of hypertensive patients. Furthermore, the polymorphism rs2536512 had been previously reported associated with an increased risk for HTN in other populations [19,20], which reinforces our findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the trend observed in the general population became more evident when only hypertensive patients were considered and the large differences in BP observed were replicated in the other population of hypertensive patients. Furthermore, the polymorphism rs2536512 had been previously reported associated with an increased risk for HTN in other populations [19,20], which reinforces our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the possible influence of common genetic variants of genes codifying for the main antioxidant enzymes has been previously explored in a few studies with discordant results. A single nucleotide polymorphism, c.172G>A (rs2536512), of the extracellular superoxide dismutase (SOD3) has been associated with an increased risk for HTN [19,20]. Furthermore, two polymorphisms in the promoter region of the catalase gene (CAT), c.-844A>G (rs769214) and c.-262T>C [21,22], and one singlenucleotide polymorphism (SNP) of the glutathione peroxidase 1 gene, c.599C>T (rs1050450), have been linked to higher values of BP, but not to elevated risk for HTN [23].…”
Section: Introductionmentioning
confidence: 99%
“…The genotype frequencies of the six SOD3 SNPs are similar in hypertensive subjects and normotensive controls. However, the rs13306703 and rs2536512 mutations are associated with essential hypertension (Naganuma et al, 2008). Two of the SOD3 SNPs present in exon 2, rs1799895 and rs2536512, are A > G missense mutations, whereas another is present in intron 1, rs17881426, and substitutes A > T. The other three SNPS are in the 5′ region: rs13306703, a C > T substitution; rs699474, an A > C/G substitution, and rs699473, which is also a C > T substitution.…”
Section: Superoxide Dismutasementioning
confidence: 99%
“…Differences in the distributions of genotypes and alleles between the CI patients and controls were analyzed using Fisher's exact test. On the basis of the genotype data of the genetic variations, we performed linkage disequilibrium analysis and haplotype-based case-control analysis, using the expectation maximization algorithm 17 and the software SNPAlyze version 3.2 (Dynacom, Yokohama, Japan). Pairwise linkage disequilibrium analysis was performed using five SNPs.…”
Section: Discussionmentioning
confidence: 99%